Supply Chains and COVID-19 Vaccines: How Fast Can We Reach Herd Immunity? - Penman, J. Adam; McMurtrey, Mark E. (Journal of Applied Business and Economics, 2024)
The COVID-19 epidemic continues to disrupt global society, but the advent of available vaccines in the Winter of 2021 meant that a return to some form of pre-pandemic “normal life” could be possible. With the supply disruptions and shortages through 2021 and 2022, the ability to both manufacture and distribute these remains important, especially with the rise of new variants and sub-variants that can evade earlier vaccines.US vaccine delivery strategies show the need to balance between focusing on delivery efficiency and delivery equity. Urban centers can focus on delivering mass numbers of vaccines quickly as these areas are often the epicenters for early stages of a pandemic, but rural areas need to focus on delivery equity over efficiency with sparsely-populated areas. Additional lessons include means to deal with vaccine-hesitant populations. This paper investigates how these changes can be implemented and the effect of current vaccine delivery with lessons for future pandemic preparation.